The genetic landscape of acute myeloid leukaemia in the South African public sector - Katherine E. Hodkinson; Pascale Willem; Mishalan Moodley; Dewaldt Engelbrecht; Pareen Patel; Tracey Wiggill; Irene Ketseoglou; Hanri Van Zijl; Jenifer Vaughan; Zivanai Chapanduka; Jaco Joubert; Jean Kloppers; et al. (South African Journal of Oncology, 2024)
Background: Acute myeloid leukaemia (AML) is a heterogeneous group of myeloid neoplasms for which two international classification systems exist: the 2022 World Health Organization (WHO) and international consensus classification of myeloid neoplasms (ICC), with an emphasis on molecular abnormalities.